Judicial quality and corporate value: evidence from China’s judicial reform - Sirui Wu; Bo Cheng; Zongtao Tian; Qinglu Jin (China Journal of Accounting Studies)
This study employs China’s judicial reform as a quasi-natural experiment to examine how judicial improvements affect corporate value. The findings reveal that: (1) compared with companies that were not affected by judicial reform, the market value of companies affected by judicial reform increased by 6.62%; (2) the reform drives corporate value through increasing investment, promoting innovation, reducing financing costs, and improving stock liquidity; (3) the effect is more pronounced for companies with poor internal control, weak board governance, low institutional investor ownership, and fewer analysts’ coverage. Our paper clarifies the causal effect between judicial reform and corporate value, complementing the previous literature on law and finance. This study bears consideration for China’s comprehensive promotion of the rule of law and the high-quality development of the capital market. It also provides empirical evidence for the necessity and importance of achieving the rule of law modernisation in emerging capital market countries.